2012
DOI: 10.1519/jsc.0b013e3182392c4b
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Demands of Competitive Surfing

Abstract: This study was a performance analysis of surfing athletes during competitive surfing events in an attempt to inform the development of surfing-specific conditioning. Twelve nationally ranked surfers were fitted with heart rate (HR) monitors and global positioning system (GPS) units and videoed during the heats of 2 sanctioned competitions. Means and SDs represented the centrality and spread of analyzed data. From the 32 videos analyzed, the greatest amount of time spent during surfing was paddling (54 ± 6.3% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
112
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(132 citation statements)
references
References 12 publications
11
112
0
Order By: Relevance
“…The Portuguese Surf Federation [4] reports that there about 10,000 federated athletes, 70 clubs and 140 surf schools in Portugal. At a competitive level, surfing requires various high intensity physical capacities, such as muscular strength and endurance, balance, postural control and neuromuscular coordination [5]; in addition surfing involves intermittent high-intensity bouts of all out paddling, to gain enough momentum for the wave take-off, interspersed with short recovery periods and repeated bouts of low-intensity paddling [6,7]. Besides of that, surfing is characterized by intermittent bouts of exercise with variation of intensity and duration that requires high muscular endurance, moderate-high cardio-respiratory endurance and recovery, and anaerobic power of the upper torso [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Portuguese Surf Federation [4] reports that there about 10,000 federated athletes, 70 clubs and 140 surf schools in Portugal. At a competitive level, surfing requires various high intensity physical capacities, such as muscular strength and endurance, balance, postural control and neuromuscular coordination [5]; in addition surfing involves intermittent high-intensity bouts of all out paddling, to gain enough momentum for the wave take-off, interspersed with short recovery periods and repeated bouts of low-intensity paddling [6,7]. Besides of that, surfing is characterized by intermittent bouts of exercise with variation of intensity and duration that requires high muscular endurance, moderate-high cardio-respiratory endurance and recovery, and anaerobic power of the upper torso [8].…”
Section: Introductionmentioning
confidence: 99%
“…To date there have been only two previous studies investigating the time-motion analysis of surfers during competition [1,6], and one study that investigated during training surf [9], and more one study in recreation surf [10]. Since the conditions of surfing are also dependent on the geographical location, it is important to carry out a timemotion analysis in the Portuguese surfers, since there is no study carried out in Portugal, and international studies are still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…While success at any level within surfing requires a high level of skill execution and technical ability [1], it is possible that physiological attributes may also be important at higher levels of performance [2]. The activity profile and the physiological demand of surfing have been previously reported [2][3][4][5]. These analyses have determined that a typical surfing session combines repeated intense anaerobic activity interspersed with aerobic exercise [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…The activity profile and the physiological demand of surfing have been previously reported [2][3][4][5]. These analyses have determined that a typical surfing session combines repeated intense anaerobic activity interspersed with aerobic exercise [3,5]. Investigations of surfing have found that various physiological and anthropometrical parameters can be used to predict performance in groups of surfers with varying levels of ability or discriminate between groups of surfers that differ in ability [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation